Utilizing AI In Indonesia's Financial Sector: Strategies For Inclusive Economic Development - Rahadi, Raden Aswin; Afgani, Kurnia Fajar; Hakam, Dzikri Firmansyah; Anggoro, Yudo; Boediman, Alfred; Indrayana, Gun Gun; Susanto, Eko (Integrasi Sains Media, 2025)
The paper explores the revolutionary potential of Artificial Intelligence (AI) in Indonesia's financial ecosystem, highlighting its capacity to improve operational efficiency, foster financial inclusion, and tackle specific socio-economic concerns. This study emphasizes Indonesia's varied demographic and digital environment, illustrating how AI-driven innovations like decentralized finance (DeFi), predictive analytics, and blockchain integration transform financial products to cater to disadvantaged people. This study utilizes over 20 scholarly publications and international case studies to highlight the strategic significance of promoting ethical AI practices, mitigating algorithmic bias, and closing infrastructural and talent disparities to achieve sustainable and inclusive economic growth. The results support implementable methods, such as public-private collaborations, strong regulatory structures, and AI-driven individualized financial solutions, to optimize the advantages of digital transformation in Indonesia's financial industry. Future research must emphasize empirical investigations into AI's capacity to mitigate financial inequalities and stimulate regional innovation, thereby establishing Indonesia as a frontrunner in AI-facilitated economic transformation.